Application of Customer Relationship Management in Emerging Economies - Maleki, Ali; Beheshtian-Ardakani, Mehdi (Journal of Entrepreneurship, Business and Economics; Vol 1 No 1/2 (2013), 2013)
Purpose- Relatively few organizations have implemented an integrated approach, which addresses all the key strategic elements of CRM. Even in more developed countries only a small number of busi-nesses have a clear idea of what they should do with information technology in order to successfully implement CRM. Design/methodology/approach- To do so, the literature is critically reviewed and main findings are presented in different categories. Findings- The role of information technology in development of a fully integrated CRM system with-in any organization is presented in the present paper. Research Implications- In many countries there is still confusion as to what CRM is all about. To some it is about a loyalty scheme, to some it is about a help desk. To others it is about a relational data base for key account management and for others it is about mass profiling the customer base without undertaking detailed segmentation. Findings highlight the realities in the area of CRM appli-cation in emerging economies and criticises the existing trends. Originality/value- The present study is among the first studies that highlights the realities in the area of CRM application in emerging economies. Conceptual paper Reference to this paper should be made as follows: Maleki, A, and Beheshtian-Ardakani, M. (2013). “Application of Customer Relationship Management in Emerging Economies”, Journal of Entrepre-neurship, Business and Economics, Vol. 1, No. 1/2, pp. 140–150.